Local Development Bank Strategies to Face Local & Global Challenges - Didi Haryono; Hanief Saha Ghafur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper discusses and analyzes the strategy and role of the Regional Development Bank, in this case the West Kalimantan Bank and its relationship in facing local and global challenges. Currently, West Kalimantan Bank is entering the Global business in the banking industry in Indonesia. The regional image attached to the Regional Development Bank gives its own color in international business competition in Indonesia. With the achievement of excellent performance from year to year, as well as international business growth opportunities, especially export-import transactions in Indonesia, making Regional Development Banks new to international business in Indonesia need to formulate the right strategy in order to survive in the face of competition with other banks. The purpose of this paper is to identify the strategies adopted by BPD in entering international business, analyze whether the strategies adopted by BPD banks in international business in Indonesia are appropriate and identify the Key Success Factors of BPD in international business. This is the biggest challenge for development banks. Regions (BPD) in encouraging regional economic competitiveness. The methodology used is qualitative with the method of literature review and interviews and the method of Focus Group Discussion. It also uses a SWOT analysis. The results obtained are a number of strategies must be carried out to increase the role of the West Kalimantan BPD in contributing to the welfare of the province of West Kalimantan.